Design professional units on maternity home of teens sheltered - Penna, Lúcia Helena Garcia (2012)
This exploratory descriptive study describes the view of government shelters’ professionals regarding pregnancy in institutionalized adolescents and discusses the acting of such professionals to support the construction of a healthy motherhood in this population group. In an investigation performed between December 2009 and January 2010, contents of the reports of six professionals that took care of them in the circles of Community Therapy sheltered adolescents were analyzed. According to the view of such professionals, motherhood in institutionalized adolescents is something precocious and harmful, resultant of the immaturity of those young mothers, and because of that, their schooling process has to be interrupted. The actions of these professionals alternates between social reintegration and care with the motherhood of the adolescents. The dialogical action, the "problematization" concerning motherhood, as well as reproductive, sexual health and family planning are strategies proposed to reach health promotion among sheltered adolescents.